The influence of curing temperature on the strength and phase assemblage of hybrid cements based on GGBFS/FA blends - Henning, Ricky; Sturm, Patrick; Geddes, Daniel A.; Keßler, Sylvia; Walkley, Brant; Gluth, Gregor J. G. (Frontiers in Materials, 2022)
Hybrid cements are composites made of Portland cement or Portland clinker and one or more supplementary cementitious materials like slag, fly ash or metakaolin, activated with an alkali salt. To date, their hydration mechanism and the phase formation at various temperatures is insufficiently understood, partly due to the large variability of the raw materials used. In the present study, three hybrid cements based on ground granulated blast furnace slag, fly ash, Portland clinker and sodium sulfate, and an alkali-activated slag/fly ash blend were cured at 10 °C and 21.5 °C, and subsequently analyzed by XRD, 27Al MAS NMR, and TGA. The compressive strength of the hybrid cements was higher by up to 27 % after 91-day curing at 10 °C, compared to curing at 21.5 °C. The experimental results as well as thermodynamic modeling indicate that the differences in compressive strength were related to a different phase assemblage, mainly differing amounts of strätlingite and C-N-A-S-H, and the associated differences of the volume of hydration products. While the strätlingite was amorphous to X-rays, it could be identified by 27Al MAS NMR spectroscopy, TGA and thermodynamic modeling. The microstructural properties of the hybrid cements and the alkali-activated slag/fly ash blend as well as the compatibility between thermodynamic modeling results and experimental data as a function of curing temperature and time are discussed.